Camera-Trapping Two Felid Species: Monitoring Eurasian Lynx (Lynx lynx) and Wildcat (Felis silvestris) Populations in Mixed Temperate Forest Ecosystems - Soyumert, Anıl (Mammalogical Society of Japan, 2020)
Documenting reliable and concrete data makes camera-trapping an appropriate tool for many secretive large mammals. Camera-trapping has been widely used for detecting the large mammal fauna of Turkey. However, systematic surveys and comprehensive assessments are still not sufficient for assessing wildlife populations in the country. In the present study, populations of Eurasian lynx (Lynx lynx) and wildcat (Felis silvestris) were monitored by systematic camera-trapping, and their co-existence was investigated with 70 camera-trap stations between 2014–2018 in northern Anatolia. Daily activity patterns and kernel density estimation were used to analyse and compare temporal patterns of target species. High temporal overlap (Δ4: 0.81) for Eurasian lynx and wildcat at the same study sites, and no alteration in wildcat activity pattern in the presence of Eurasian lynx, suggest that these two felid species can co-exist in the same habitats using the same period of the day. Domestic cat (Felis catus) was detected at 52.5% of the wildcat-positive stations indicating that there is hybridisation threat for the wildcat population in the region. The study reveals that systematic camera-trapping surveys are an applicable method for monitoring cryptic mammalian carnivores and provide useful insights into the threats on wildlife populations like hybridisation.
Keywords: 14. Life underwater; 15. Life on land